ANALISIS FAKTOR RISIKO YANG BERPENGARUH TERHADAP KEJADIAN POSTPARTUM BLUES PADA IBU POSTPARTUM DI PUSKESMAS WILAYAH KERJA KOTA YOGYAKARTA - , DIAH AYU FATMAWATI, Heny Suseani P, S.Kp., M.Kes. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background. During the postpartum period, about 80% of women will experience a variety of disorders feelings, if it does not get proper treatment will continue into the postpartum blues, postpartum depression to postpartum psychosis. The purpose of this research was to identify risk factors that affect the incidence of postpartum blues at community health center working area city of Yogyakarta. Materials and Method. This study was non-experimental studies using crosssectional study design with quantitative and qualitative approaches. Subjects in the study of postpartum maternal at community health center working area city of Yogyakarta amounted to 80 respondents in January-March 2014. Sampling technique with accidental sampling. Data collection using questionnaires Edinburgh Postnatal Depression Scale (EPDS), social support husband questionnaire and in-depth interviews. Data were analyzed using chi-square statistical test and logistic regression. Research results. The proportion of postpartum blues in the community health center working area city of Yogyakarta is 46%. Risk factors for maternal age (p=0.000, RP=3.41), parity (p=0.007, RP=1.94) and social support the husband (p=0.000, RP=2.44) had a significant effect on incidence of postpartum blues. Risk factors of education (p=0.152), maternal employment status (p=0.282), the type of labor, unplanned pregnancy (p=0.908) and family economic status (p=0.342) had no significant effect on the incidence of postpartum blues. Multivariate results showed maternal age factor is the most powerful risk factors affect the incidence of postpartum blues. Conclusion. Risk factors for maternal age, parity and social support the husband has a significant influence on the incidence of postpartum blues. Maternal age is the strongest risk factor effect on the incidence of postpartum blues.